Some Topological Properties of CbX. (21st December 2014) - Ferrando, Juan Carlos
Abstract : IfX is a completely regular space, first we characterize those spacesC b X whose compact sets are metrizable. Then we use this result to provide a general condition forX to ensure the metrizability of compact sets inC b X . Finally, we characterize those spacesC b X that have aG -basis.